Domestic dialogue and its relationship with Self- Transcendence among pupils of grade praimary (Journal Of Educational and Psychological Researches, 2017)
The dialogue considers a method and life curriculum help to solve many problems as well as the best way to build a healthy family setting supports the growth of children and leads to the formation sound, strong and positive character. It also supports the family relationship. many of family members needs may achieve through what prevails among them such as continuing a comprehensive and deep combines word, deed and feeling it enters the body and soul . So each part strengthens by the other part and exchanges effect The deep domestic dialogue opens hearts between parents and children  Family increases more loving , intimacy , honesty and happiness. So the domestic dialogue became an urgent necessity in the light of many social changes taking place in communities led to loss continuity between parents and children at a time when the need to increase dialogue especially after the spread of communications and means of various media revolution.The self-transcendence represents one of the important variables in personality , human transcendence and advancement results from the orientation of psychological strength to the absolute good that makes him pure , clear and humble. The intellectual purity leads to a great mental self-transcendence .i.e to develop the biological energy (material ) spiritual energy ( self-transcendence ) . The lofty energy that we need to control our emotions and to put an end of anxiety which became social phenomenon permeate in human life and makes him a creature interested in achievement of physical and virual existence only.The researchers built two measures : The first is for domestic dialogue and the second is for self-transcendence then the scale was applied to a sample of             ( 500 ) pupils; male and female in sixth grade they were selected at random from the research community . After collecting the data were processed using appropriate statistical methods. The researchfound the following results :- The pupils enjoy high level dialogue of the family. There is no difference in the domestic dialogue on according to gender and congenital arrangement. The pupils enjoy high level of self-transcendence There is no difference in self-transcendence according to gender and congenital arrangement. There is a positive correlation between the level of family dialogue and the level .(self-transcendence) reliance among sixth grade pupils.In light of the present results the researchers made a number of recommendations and a suggestions.